The Isle of Sculptures of Pontevedra (1999-2019): a model to recover nature as a social and cultural space in the city - Castro-Fernández, X. Antón; Herranz Pascual, Yolanda; Pastor-Bravo, Jesús (Arte, Individuo y Sociedad, 2022)
The Isle of Sculptures was created as a cultural construction of nature and reverted to an aesthetic landscape, taking in consideration the ethnographic, historical and anthropological uniqueness of the place where it is located: the Xunqueira del Lérez in Pontevedra. At the same time, it is a tribute to the identifying material of sculpture from all eras and a reference to culture and art that its authors connect with the mythical consciousness and symbolism of The Waste Land by T. S. Eliot. Just as in The Waste Land, which reunites past and present, with metaphors and symbols, the sculptors who take part in the space outlined by the Lérez River embrace, as a whole, a plurality of cultural allusions, languages and concepts, classical references and more contemporary experiences. Twelve artists were invited to take part: Giovanni Anselmo, Fernando Casás, José Pedro Croft, Dan Graham, Ian Hamilton Finlay, Jenny Holzer, Francisco Leiro, Richard Long, Robert Morris, Anne & Patrick Poirier, Ulrich Rückriem y Enrique Velasco.